Sonoluminescence Spectra in the First Tens of Seconds of Sonolysis of [BEPip][NTf2], at 20 kHz under Ar - Rachel Pflieger; Manuel Lejeune; Micheline Draye (Molecules, 2022)
Following recent works on the sonochemical degradation of butyl ethyl piperidinium bis-(trifluoromethylsulfonyl)imide ([BEPip][NTf2]), monitoring of sonoluminescence (SL) spectra in the first tens of seconds of sonolysis was needed to better characterize the formed plasma and to question the correlation of the SL spectra with the viscosity. A very dry [BEPip][NTf2] ionic liquid (IL) and a water-saturated liquid are studied in this paper. In both cases, IL degradation is observed as soon as SL emission appears. It is confirmed that the initial evolution of the SL intensity is closely linked to the liquid viscosity that impacts the number of bubbles; however, other parameters can also play a role, such as the presence of water. The water-saturated IL shows more intense SL and faster degradation. In addition to the expected bands, new emission bands are detected and attributed to the S2 B-X emission, which is favored in the water-saturated ionic liquid.